Substitusi Tepung Terigu dengan Tepung Kacang Hijau (Vigna radiata L) Terhadap Sifat Kimia dan Organoleptik pada Produk Cookies - Bertina, Bernadeta Wiska Pramestia; Laswati, Dyah Titin; Rukmini, Ambar; masrukan (AGROTECH : JURNAL ILMIAH TEKNOLOGI PERTANIAN, 2024)
The utilization of green bean flour in cookie products has the potential to be developed as a food innovation and as a functional food. This research aims to determine the protein and fibre content of the cookies produced and to diversify the Indonesian people's dependence on imported raw materials (wheat flour). This research used the RAK (Randomized Block Design) 1 factorial method consisting of 6 treatments, namely 0%, 15%, 30%, 45%, 60% and 75%. Each treatment was subjected to chemical tests (moisture, ash, fat, protein, crude fibre and carbohydrate content) and organoleptic tests (scoring test and hedonic test). The results of the data obtained are then analyzed statistically using Analysis of Variance (ANOVA). If there is a significant difference, the Duncan Multiple Range Test (DMRT) will be carried out with a 5% follow-up test. The results of this research indicate that chemical and organoleptic changes occurred. Based on the test parameters, the most acceptable cookie treatment is the 45% treatment. The chemical test results obtained were as follows: Water 3.94 (%), ash 1.32 (%db), fat 30.06 (%db), protein 10.23 (%db), crude fibre (%db), and carbohydrates 45.10 (%db). The organoleptic test results were obtained at 3.76.